2005
DOI: 10.1007/s11121-005-0013-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Child Behavior Problems Through Universal Implementation of a Group Behavioral Family Intervention

Abstract: The aim of this mental health promotion initiative was to evaluate the effectiveness of a universally delivered group behavioral family intervention (BFI) in preventing behavior problems in children. This study investigates the transferability of an efficacious clinical program to a universal prevention intervention delivered through child and community health services targeting parents of preschoolers within a metropolitan health region. A quasiexperimental two-group (BFI, n = 804 vs. Comparison group, n = 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
161
2
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(170 citation statements)
references
References 39 publications
3
161
2
4
Order By: Relevance
“…Randomization, or even being able to have a control group, is difficult to attain due to the requirements of the participating entities. The use of participants from a neighboring area with characteristics similar to those of the intervention group as a control group, as in our case, is an option already used in other effectiveness trials in prevention (Zubrick et al, 2005). This option can help avoid a "spillover" effect, and possible demographic differences could be controlled with strategies in place to match samples for demographic characteristics, or through covariate analyses (Yager et al, 2013).…”
Section: Elsevier_brt_2937mentioning
confidence: 99%
“…Randomization, or even being able to have a control group, is difficult to attain due to the requirements of the participating entities. The use of participants from a neighboring area with characteristics similar to those of the intervention group as a control group, as in our case, is an option already used in other effectiveness trials in prevention (Zubrick et al, 2005). This option can help avoid a "spillover" effect, and possible demographic differences could be controlled with strategies in place to match samples for demographic characteristics, or through covariate analyses (Yager et al, 2013).…”
Section: Elsevier_brt_2937mentioning
confidence: 99%
“…The authors searched Google Scholar, PubMed and Web of Science for studies published in the last 20 years with the key words universal, preventive, parent/al, training, management, program/s , programme/s (minus, school, cancer, tobacco, alcohol, new-born, hearing, media); and found no study that had intervention groups that participated in a parent training program included in the current study. However, six studies (Cann, Rogers, & Matthews, 2003;Hiscock et al, 2008;Kendall, Bloomfield, Appleton, & Kitaoka, 2013;Geoff Lindsay & Strand, 2013;Neville et al, 2013;Zubrick et al, 2005) investigated the effect of similar programs. However, the three studies by Zubrick, Hiscock and Neville et al each took place within a socioeconomically deprived region, and were associated with significant reductions in parent-reported levels of dysfunctional parenting (Zubrick et al) and stress (Neville et al).…”
Section: Introductionmentioning
confidence: 99%
“…This program of research has shown successful outcomes with a number of populations and problem areas, with consistent improvement in quality of parenting across studies (e.g., Bor et al 2002;Sanders and McFarland 2000). Triple P has been evaluated as a universal, whole of population strategy and shown to strengthen parenting and reduce the prevalence of conduct problems in preschool-aged children from high-risk neighborhoods (Zubrick et al 2005), and to reduce coercive parenting practices through the implementation of multiple levels of Triple P . Several effectiveness and dissemination studies have been conducted on Triple P demonstrating portability and broad utility in multiple settings (Sanders et al 2003a, b;Turner and Sanders 2006;Zubrick et al 2005).…”
mentioning
confidence: 99%
“…Triple P has been evaluated as a universal, whole of population strategy and shown to strengthen parenting and reduce the prevalence of conduct problems in preschool-aged children from high-risk neighborhoods (Zubrick et al 2005), and to reduce coercive parenting practices through the implementation of multiple levels of Triple P . Several effectiveness and dissemination studies have been conducted on Triple P demonstrating portability and broad utility in multiple settings (Sanders et al 2003a, b;Turner and Sanders 2006;Zubrick et al 2005). Additionally, several independent replications of Triple P implementation and findings in diverse cultural contexts have been conducted (Bodenmann et al 2008;Cann et al 2003;Crisante and Ng 2003;Dean et al 2003;Gallart and Matthey 2005;Heinrichs et al 2005Heinrichs et al , 2006aLeung et al 2003;Rogers et al 2003;Turner et al 2007).…”
mentioning
confidence: 99%